2013
DOI: 10.1002/ijc.28271
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of ADAMTS1 as a tumor suppressor gene in human breast carcinoma. Linking its tumor inhibitory properties to its proteolytic activity on nidogen‐1 and nidogen‐2

Abstract: The extracellular protease ADAMTS1 (A disintegrin and metalloprotease with thrombospondin repeats 1) has been described as an anti-angiogenic molecule and its role as a putative tumor protective molecule has also been suggested. Here, we have used a tumor xenograft model to determine the role of ADAMTS1 in tumor growth and angiogenesis. Increasing levels of the protease led to the complete inhibition of tumor growth. In an attempt to elucidate the mechanism of action of this protease, we focused our attention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 38 publications
6
26
0
Order By: Relevance
“…On the other hand, NID1 may be modified in the ECM by the action of extracellular proteases, such as Cat-S and ADAMTS1 (A Disintegrin and Metalloproteinase with ThromboSpondin motifs). 70 In addition, NID1 can interact with different BM/ECM proteins including laminin, collagen type IV, and perlecan. 57,58 Thus, it is possible that the tissue microenvironment and the molecular context may further influence the functional outcome of the NID1-NKp44 interaction.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, NID1 may be modified in the ECM by the action of extracellular proteases, such as Cat-S and ADAMTS1 (A Disintegrin and Metalloproteinase with ThromboSpondin motifs). 70 In addition, NID1 can interact with different BM/ECM proteins including laminin, collagen type IV, and perlecan. 57,58 Thus, it is possible that the tissue microenvironment and the molecular context may further influence the functional outcome of the NID1-NKp44 interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, ADAMTS1 was found to be relevant during endothelial cell sprouting in collagen invasion assays [15], and its expression is induced in endothelial cells under hypoxic conditions and VEGF-treatment [16, 17]. The specific influence of stromal ADAMTS1 has been suggested in some studies of breast cancer [4, 18, 19], and the use of the ADAMTS1 knockout mice, in combination with a spontaneous model of mammary carcinogenesis, revealed its participation in tumor growth and metastasis [7]. …”
Section: Introductionmentioning
confidence: 99%
“…ADAMTS1 also cleaves large TSP1, and cleaved TSP-1 demonstrates anti-angiogenic activity (26). Several studies have also demonstrated that ADAMTS1 is downregulated in breast cancer, prostate cancer, lung cancer, pancreatic cancer and colorectal cancer (1820,25,27,28). These findings are in accordance with our previous study, in which the expression of ADAMTS1 was frequently reduced in primary gastric cancer (22).…”
Section: Discussionmentioning
confidence: 99%
“…ADAMTS1 inhibits angiogenesis through binding to vascular endothelial growth factor (VEGF) 165 and inhibiting VEGF-A165-stimulated phosphorylation of VEGFR-2 (17). In addition, it has decreased expression levels in a number of types of cancer (8,1820), however, the underlying mechanism remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%